PENGARUH PENGETAHUAN, PENDAPATAN, DAN RELIGIUSITAS TERHADAP MINAT MUZAKKI DALAM MEMBAYAR ZAKAT PENGHASILAN DI KOTA DEPOK DENGAN FAKTOR USIA SEBAGAI VARIABEL MODERASI - Putri Febriyanti; Sulistyowati Sulistyowati (Journal of Accounting, Management and Islamic Economics, 2024)
This research aims to empirically test the variables in the research that is whether there is influence between knowledge, income, and religiosity on the interest of muzakki paying income zakat, with an age factor as a moderator variable. The sample in this research were muzakki in Depok City amounting 114 respondents. This type of research is field research by questionnaire. The data analysis technique used was moderartion regression analysis (MRA) it uses SPSS software version 25 to test the relationship of variables. From the results of the T (partial) test in this research it is known that only knowledge and religiosity that has a significant effect on the interest of muzakki to paying income zakat in Depok City. Income does not affect the interest of muzakki paying income zakat in Depok City. The age factor is can to moderate the influence of knowledge and religiosity on the interest of muzakki to pay income zakat in Depok City. The age factor is can not to moderate the influence of income on the interest of muzakki to pay income zakat in Depok City. From the results of the F (simultaneous) test in this research it is known that the knowledge, income, and religiosity simultaneously has a significant effect on the interest of muzakki to paying income zakat on Depok City moderated by the age factor.